Continuity of the formative process during pandemic times. Student experience at Los Lagos University, Chile - Lemarie Oyarzun, Fernando Rodolfo (2022)
This article analyzes the opinions of students of the Universidad de Los Lagos, Osorno, Chile, on the actions implemented to ensure the continuity of the formative process during the academic year 2020, in the dimensions of technological deployment and teaching-learning experience. The above, as a response to the pandemic, which forced the Higher Education Institutions to make emerging decisions and thus obtain feedback to support the implementation of improvements and the creation of permanent programs to maintain quality academic training. The research methodology applied was mixed. For the quantitative component, data were collected through the application of an online questionnaire to 1,492 students. For the qualitative component, semi-structured interviews and focus groups were conducted with 25 key informants. The results showed timely and dynamic actions that allowed the prompt availability of the Moodle platform, ULAGOS Virtual, for the continuity of the teaching-learning process. They also reflected the regional deployment for the delivery of mobile devices and Internet connection kits that enabled the connectivity and continuity of online studies. They also revealed gaps in access to technologies, challenges related to the stress of the context and social and economic inequalities.